An atomistic perspective on antibody-dependent cellular cytotoxicity quenching by core-fucosylation of IgG1 Fc N-glycans from enhanced sampling molecular dynamics. (12th December 2019) - Harbison, Aoife; Fadda, Elisa
Abstract: The immunoglobulin type G (IgG) Fc N-glycans are known to modulate the interaction with membrane-bound Fc γ receptors (FcγRs), fine-tuning the antibody's effector function in a sequence-dependent manner. Particularly interesting in this respect are the roles of galactosylation, which levels are linked to autoimmune conditions and aging, of core fucosylation, which is known to reduce significantly the antibody-dependent cellular cytotoxicity (ADCC), and of sialylation, which also reduces antibody-dependent cellular cytotoxicity (ADCC) but only in the context of core-fucosylation. In this article, we provide an atomistic level perspective through enhanced sampling computer simulations, based on replica exchange molecular dynamics (REMD), to understand the molecular determinants linking the Fc N-glycans sequence to the observed IgG1 function. Our results indicate that the two symmetrically opposed N-glycans interact extensively through their core trimannose residues. At room temperature, the terminal galactose on the α (1–6) arm is restrained to the protein through a network of interactions that keep the arm outstretched; meanwhile, the α (1–3) arm extends toward the solvent where a terminal sialic acid remains fully accessible. We also find that the presence of core fucose interferes with the extended sialylated α (1–3) arm, altering its conformational propensity and as a consequence of steric hindrance, significantly enhancing the Fc dynamics. Furthermore, structural analysis shows that the core-fucose position within the Fc core obstructs the access of N162 glycosylated FcγRs very much like a "door-stop, " potentially decreasing the IgG/FcγR binding free energy. These results provide an atomistic level-of-detail framework for the design of high potency IgG1 Fc N-glycoforms.